The Demarcation of Land and the Role of Coordinating Property Institutions - Libecap, Gary D.; Lueck, Dean (Journal of Political Economy, 2011)
We use a natural experiment in nineteenth-century Ohio to analyze the economic effects of two dominant land demarcation regimes, metes and bounds (MB) and the rectangular system (RS). MB is decentralized with plot shapes, alignment, and sizes defined individually; RS is a centralized grid of uniform square plots that does not vary with topography. We find large initial net benefits in land values from the RS and also that these effects persist into the twenty-first century. These findings reveal the importance of transaction costs and networks in affecting property rights, land values, markets, and economic growth.